2021
DOI: 10.4070/kcj.2021.0100
|View full text |Cite
|
Sign up to set email alerts
|

Global Awareness of Myocardial Infarction Symptoms in General Population: a Systematic Review and Meta-Analysis

Abstract: Author's summary Seventy percent people are able to recognize chest pain as myocardial infarction (MI) symptoms. There is no difference in awareness of MI symptoms between male and female. There is wide variation in awareness of MI symptoms. The prevalence varies from less than 5% in African countries such as Kenya, Tanzania and in Asian countries such as Nepal to as high as 90% in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, during tele-triage, patients may provide inaccurate history [ 40 ] as TMD is difficult to be described by the patient. In addition, it could be an early symptom of an underlying cardiac problem [ 41 ]. Given such uncertainties combined with the fact that our TD was largely limited to telephone consultations during the pandemic's initial stages like other places worldwide [ 39 ], half of our TMD cases were referred.…”
Section: Discussionmentioning
confidence: 99%
“…However, during tele-triage, patients may provide inaccurate history [ 40 ] as TMD is difficult to be described by the patient. In addition, it could be an early symptom of an underlying cardiac problem [ 41 ]. Given such uncertainties combined with the fact that our TD was largely limited to telephone consultations during the pandemic's initial stages like other places worldwide [ 39 ], half of our TMD cases were referred.…”
Section: Discussionmentioning
confidence: 99%
“… 14) In Japan, only 11.6% of the 1,200 participants surveyed were aware of the need to call EMS promptly for AMI symptoms. 15) More broadly, a meta-analysis by Sharma et al 16) reported a wide variation in the prevalence of awareness of chest pain as a symptom of MI in various Asian countries.…”
Section: Pre-hospital Carementioning
confidence: 99%
“…Myocardial infarction (MI) is an important cause of mortality and morbidity worldwide [ 78 ]. MI is cited among the major causes of AF [ 4 ].…”
Section: Thyroid Disease-associated Cardiac Comorbidities and Af Riskmentioning
confidence: 99%